ADOPTION OF SKPI IMPLEMENTATION POLICY TO ENCOURAGE STRENGHTEEN OF STUDENTS SOFT SKILL DEVELOPMENT - Murtadlo, Mu'tashim Billah; Wijiharta, Wijiharta (At-Tauzi : Jurnal Ekonomi Islam, 2022)
This study aims to conduct a study on the adoption of skpi implementation policies and their role in encouraging the mastery of student soft skills. This review of the literature review using the HPP program tool (Harzing's Publish or Perish 8) and Google Content review of 48 scientific documents resulted in 29 articles that were reduced, verified, presented and inferred. The results of the study resulted in a note that (1) the SKPI policy encourages universities to facilitate soft skills planting programs, convert reporting of extra-curricular and non-curricular activities into the SKPI format, (2) the adoption of universities to skpi policies is expected to encourage mastery of student soft skills, (3) SKPI policies encourage universities to provide a SKPI / TAK information system that can optimize their use to overseeing the development of academic competencies, soft skills, hard skills and student personalities to match the personal road map that has been designed since the early stages of education